Pengaruh Marketing Mix Terhadap Volume Pembelian Produk Singkong Keju di UMKM Argotelo Kota Salatiga - Prasetyo, Annisa Shifa; Mariyono, Joko; Budiraharjo, Kustopo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Micro, Small and Medium Enterprises (UMKM) in the field of agricultural product processing such as cassava have great potential to be developed through product innovation, effective marketing and good management. This study aims to analyze the effect of the marketing mix (4P) namely product, price, place and promotion on the purchase volume of cassava cheese in Argotelo Salatiga. The location of the study was at UMKM Argotelo in Argomulyo District, Salatiga City. The study used a case study with a sample determination method using Accidental Sampling of 100 respondents. The data collection was carried out by interviewing using a questionnaire. Data collection techniques used descriptive analysis and multiple regression analysis. The results of this study indicate that the 4P marketing mix (product, price, place and promotion) simultaneously has a significant effect on purchase volume. The price variable partially has a significant effect on the purchase volume of cassava cheese. While the product, place and promotion variables partially do not affect the purchase volume of cassava cheese in Argotelo Salatiga.